PENGARUH ORIENTASI PASAR TERHADAP KINERJA PEMASARAN MELALUI INOVASI PRODUK DAN KEUNGGULAN BERSAING PADA OUTLET KOSMETIK DI KOTA SEMARANG - Permata, Fanindia; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2019)
This research was carried out because of a business phenomenon from TopBrand. It can be seen that sales of several cosmetic products have increased and decreased sales over the past 3 years. Both Revlon, Pixy and Wardah compete with each other for their products. But Wardah himself experienced an increase in the top brand index from 2015 to 2017. This is the reason in this study choosing research objects in Wardah, Revlon and Pixy outlet cosmetics in the city of Semarang. The research objective was to find out empirically the effect of market orientation on product innovation and competitive advantage and its impact on marketing performance at the Cosmetic Outlet in the city of Semarang.The research sample was 150 respondents. Data was taken using a questionnaire distributed to Cosmetic Outlets in Semarang City. The sampling method used was purposive sampling technique, namely sampling based on established criteria, among others: Cosmetic outlets in the city of Semarang, minimum standing for 2 years and willing to be used as respondents. The data analysis method uses structural equation modeling using AMOS software.The test results show that there is a significant and positive influence of market orientation on product innovation, there is a significant and positive influence of market orientation on competitive advantage, there is a significant and positive influence of product innovation on marketing performance, and there is a significant and positive influence on competitive advantage on marketing performance.